MANAJEMEN SANTRI DI PONDOK PESANTREN: KAJIAN LITERATUR TENTANG PEMBINAAN MORAL DAN KEDISIPLINAN SANTRI - Afaf Sya’roni; Muhammad Aminullah (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
The rapid flow of digital technology disruption and the widespread shift in religious moral values ​​among the coastal youth generation are the background to this article. These operational issues have triggered a vulnerability to personality crises, a fading of daily cyber social ethics, and the inefficiency of conventional supervisory systems within the dormitory environment. The main focus of this scientific study is to examine the implementation of administrative governance and formulate an effective managerial strategy for reconstructing moral development and fostering discipline among students. This qualitative research, using a library review, was conducted through a structured search of secondary literature from a database of reputable scientific journals spanning the years 2020 to 2026. The data synthesis procedure was executed using a functional interactive analysis model that integrates planning, organizing, implementation, and control parameters. Empirical research findings reveal that a hybrid collaborative approach, conditioning the draft of reward and punishment instruments, and strengthening the mentoring method of the kiai (Islamic teacher) have proven effective in boosting student academic resilience. Logistical obstacles, such as limited operational funds, were overcome through diversification of the Islamic boarding school's independent business units. The main conclusion confirms that adaptive student administration standards have successfully maintained the existence of Islamic boarding schools (pesantren) as bastions of national morality in the modern era. Institutional administrators are recommended to draft a consistent cyber ethics curriculum. ABSTRAK Derasnya arus disrupsi teknologi digital serta maraknya pergeseran nilai-nilai moralitas keagamaan di kalangan generasi muda pesisir melatarbelakangi penulisan artikel ini. Masalah operasional tersebut memicu kerentanan krisis kepribadian, pudarnya etika bersosial siber harian, serta inefisiensi sistem pengawasan konvensional di lingkungan asrama. Fokus utama kajian ilmiah ini adalah membedah implementasi tata kelola kepengurusan serta merumuskan draf strategi manajerial yang efektif dalam merekonstruksi pembinaan moral dan pembentukan kedisiplinan santri. Langkah-langkah penelitian kualitatif dengan jenis studi kepustakaan (library review) ini dioperasikan melalui penelusuran draf literatur sekunder secara terstruktur dari basis data jurnal ilmiah bereputasi dalam rentang tahun 2020 hingga 2026. Prosedur sintesis data dieksekusi memakai model analisis interaktif fungsional yang mengintegrasikan parameter perencanaan, pengorganisasian, pelaksanaan, serta pengendalian. Temuan riset secara empiris menyingkap bahwa hibridasi pendekatan kolaboratif, pengondisian draf instrumen penghargaan dan hukuman, serta penguatan metode mentoring figur kiai terbukti andal dalam mendongkrak ketahanan akademik siswa. Hambatan logistik berupa keterbatasan dana operasional diatasi melalui diversifikasi unit usaha mandiri pesantren. Simpulan utama menegaskan bahwa standardisasi administrasi kesiswaan yang adaptif sukses mempertahankan eksistensi pesantren sebagai benteng moralitas bangsa di era modern. Pengelola lembaga direkomendasikan menyusun draf kurikulum etika siber secara konsisten.